Deciding How To Decide: Self-Control and Meta-Decision Making. Issue 11 (November 2015) - Boureau, Y-Lan; Sokol-Hessner, Peter; Daw, Nathaniel D.
Abstract : Many different situations related to self control involve competition between two routes to decisions: default and frugal versus more resource-intensive. Examples include habits versus deliberative decisions, fatigue versus cognitive effort, and Pavlovian versus instrumental decision making. We propose that these situations are linked by a strikingly similar core dilemma, pitting the opportunity costs of monopolizing shared resources such as executive functions for some time, against the possibility of obtaining a better outcome. We offer a unifying normative perspective on this underlying rational meta-optimization, review how this may tie together recent advances in many separate areas, and connect several independent models. Finally, we suggest that the crucial mechanisms and meta-decision variables may be shared across domains. Trends: Meta-decisions are decisions about how decisions are made. Many recent models in different domains have conceptualized meta-decision dilemmas as pitting more carefully computed decisions against automatic defaults, including goal-directed versus habitual responses, deliberative versus heuristic choices, and controlled versus impulsive actions. These recent models show that many puzzling decision patterns as well as phenomena of self-control and conflict can be understood as rational arbitration that balances the potentially better outcomes of more considered decisions against the higher costs of such consideration. A central cost of deliberation across many seemingly separate domains has been proposed to be the opportunity cost of occupying shared resources over time. Common decision variables and mechanisms may guide these allocations across many such domains.